Graphene: Improved Graphitic Structure of Continuous Carbon Nanofibers via Graphene Oxide Templating (Adv. Funct. Mater. 46/2013). (10th December 2013) - Papkov, Dimitry; Goponenko, Alexander; Compton, Owen C.; An, Zhi; Moravsky, Alexander; Li, Xing‐Zhong; Nguyen, SonBinh T.; Dzenis, Yuris A.
<x xml:space="preserve">Abstract</x> Graphene oxide sheets get anisotropically crumpled and oriented by radial and shear forces in fast‐thinning electrospun jets. On page 5763, Y. Dzenis and co‐workers demonstrate that a small fraction of these nanoparticles in polyacrylonitrile precursor nanofibers can produce global improvements of the graphitic order and orientation in the resulting carbon nanofilaments. Such a templating methodology utilizing low‐cost constituents, efficient top‐down nanomanufacturing, and relatively low carbonization temperatures may lead to inexpensive continuous carbon nanofibers with improved mechanical and transport properties. Artwork by Joel Brehm. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>